P542 Efficacy and safety of biological therapies in chronic antibiotic-refractory pouchitis: a retrospective single-centre experience. (25th January 2019) - Verstockt, B; Claeys, C; Van Assche, G; D'Hoore, A; Wolthuis, A; Vermeire, S; Ferrante, M
Abstract: Background: Chronic antibiotic-refractory pouchitis affects up to 15% of patients with ulcerative colitis (UC) following colectomy with ileal pouch-anal anastomosis (IPAA). In retrospective series, infliximab (IFX), adalimumab (ADM) and vedolizumab (VDZ) have demonstrated efficacy, but data are limited. We here report single-centre data of biological therapy in refractory pouchitis. Methods: We retrospectively assessed all records from UC patients who underwent IPAA and were exposed to IFX, ADM or VDZ thereafter at our centre. Patients with a baseline modified pouchitis disease activity index (mPDAI)< 5 or with Crohn's disease-related complications of the pouch were excluded. Clinically relevant remission, defined as a mPDAI <5 and a reduction of mPDAI 2 points from baseline, was assessed at Week 14. Non-responder imputation was applied in case of discontinuation prior to Week 14. Results: Thirty-three unique patients were included (69.7% male, median [IQR] age 39.6 [33.7–52.8]). Three (9.1%) underwent colectomy because of high-grade dysplasia, whereas 90.9% had surgery due to refractory UC. Prior to surgery, patients had been exposed to cyclosporine ( n = 14), IFX ( n = 12), ADM ( n = 3), and/or VDZ ( n = 3). J-pouches were constructed mainly in (modified) 2-stage ( n = 25) procedures. All developed chronic antibiotic-refractory pouchitis after a median of 3.1 years, for which they received IFX ( n = 23), ADM ( n = 13) or VDZ ( n = 15). Clinically relevant remission at Week 14 was observed in 43.5% of IFX group, and 38.5% and 60.0% in the ADM and VDZ group. With a median follow-up of 1.0 (0.3–3.1) years, significantly more patients continued VDZ compared with anti-TNF therapy (HR 2.9 [95% CI 1.1–8.5], p = 0.04) (figure). Kaplan–Meier curve representing the biological therapy discontinuation-free survival in chronic antibiotic-refractory pouchitis Compared with baseline, VDZ resulted in a significant drop in endoscopic PDAI score at final follow-up ( p = 0.004), whereas IFX and ADM led to a more modest drop ( p = 0.03, p = 0.1, respectively). Adverse events (mainly infusion reactions) and undetectable serum levels explained 48.1% of the patients discontinuing anti-TNF therapy, whereas discontinuation of VDZ was only related to insufficient efficacy. Overall, 4 patients (12.1%) ended up with a permanent ileostomy. Conclusions: In this case series, the use of anti-TNF agents for the treatment of chronic antibiotic-refractory pouchitis was hampered by the high rate of adverse events partly related by pre-colectomy exposure to the same drug. Therefore, VDZ might be an efficacious and safe alternative, which is currently being studied in a phase IV randomised trial.